2020
DOI: 10.3390/vaccines8010084
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Immunoprotective Potential of Recombinant Paraflagellar Rod Proteins of Trypanosoma evansi in Mice

Abstract: Trypanosomosis, caused by Trypanosoma evansi, is an economically significant disease of livestock. Systematic antigenic variation by the parasite has undermined prospects for the development of a protective vaccine that targets the immunodominant surface antigens, encouraging exploration of alternatives. The paraflagellar rod (PFR), constituent proteins of the flagellum, are prominent non-variable vaccine candidates for T. evansi owing to their strategic location. Two major PFR constituent proteins, PFR1 (1770… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 69 publications
(80 reference statements)
0
1
0
Order By: Relevance
“…Strategies included intracellular targets inaccessible to antibody attack (such as tubulin) and implemented most often extremely short waiting periods between boost and challenge, making it hard to grasp which immunological principle would have been triggered to provide protection. A recent study on the use of the T. evansi paraflagellar rod proteins PFR1 and PFR2, in which the infection challenge was performed only 7 days after the last vaccine boost, showed that the presence of high anti-target IgG titers at the moment of parasite challenge could delay the onset of parasitemia, but in the end failed to provide any sterile protection [ 103 ]. Most recently, it was shown that an anti- T. vivax vaccine using the ectodomain of the invariant cell-surface flagellum antigen IFX conferred protection against a subsequent T. vivax challenge in 10/15 mice, and that protection was observed even when parasite challenges were performed repeatedly over a 100-day period following the last vaccine boost.…”
Section: Discussionmentioning
confidence: 99%
“…Strategies included intracellular targets inaccessible to antibody attack (such as tubulin) and implemented most often extremely short waiting periods between boost and challenge, making it hard to grasp which immunological principle would have been triggered to provide protection. A recent study on the use of the T. evansi paraflagellar rod proteins PFR1 and PFR2, in which the infection challenge was performed only 7 days after the last vaccine boost, showed that the presence of high anti-target IgG titers at the moment of parasite challenge could delay the onset of parasitemia, but in the end failed to provide any sterile protection [ 103 ]. Most recently, it was shown that an anti- T. vivax vaccine using the ectodomain of the invariant cell-surface flagellum antigen IFX conferred protection against a subsequent T. vivax challenge in 10/15 mice, and that protection was observed even when parasite challenges were performed repeatedly over a 100-day period following the last vaccine boost.…”
Section: Discussionmentioning
confidence: 99%